The afterglows of whole school development in Ghana: a case study of semi-rural municipality - Ghartey, Seth Baisie. (2011)
It is nearly ten years ago when Whole School Development (WSD) in Ghana was officially ended. Yet, most of its structures, systems and practices continue to function in the country. This thesis is based on data collected from a case study of a semi-rural municipality of the country regarding the reasons for its official ending and why despite its official ending, most of the structures, systems and practices continue to function. The thesis also indicates which of the structures, systems and practices are functioning and how well they are functioning.